1980
DOI: 10.1203/00006450-198006000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hormones on the Biochemical Development of Fetal Rat Lung in Organ Culture. II. Insulin

Abstract: Summary ated species of this phospholipid is believed to play a major role In lowering surface tension at the air-alveolar interface, thereby PC in the lungs of the fetuses of glucose-intolerant monkeys. InInsulin treatment had no effect on the rate of choline incorpoaddition, Moxley and L~~~~~~~ found ,hat glucose ration into phosphatidylcholine (PC) or disaturated PC and did into PC in isolated, perfused rat lungs was decreased not antagonize the dexamethasone-induced stimulation of choline when the lungs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…During maternal diabetes, the fetus is exposed to hyperglycaemia and hyperinsulinaemia [37][38][39][40], both of which inhibit glycogenolysis and lower synthesis of surfactant phospholipids in fetal lungs [9,11,12]. In the present study, rat fetuses were exposed to hyperglycaemia which subsided to almost normal serum glucose levels in newborn after parturition (Table 1).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…During maternal diabetes, the fetus is exposed to hyperglycaemia and hyperinsulinaemia [37][38][39][40], both of which inhibit glycogenolysis and lower synthesis of surfactant phospholipids in fetal lungs [9,11,12]. In the present study, rat fetuses were exposed to hyperglycaemia which subsided to almost normal serum glucose levels in newborn after parturition (Table 1).…”
Section: Discussionmentioning
confidence: 75%
“…Synthesis of surfactant phospholipids appears to be dependent on metabolism of glucose [3][4][5] and glycogen [6][7][8][9] as they provide dihydroxyacetone phosphate and a-glyceraldehyde phosphate, which are precursors of phospholipid synthesis in lungs [6,9,10]. In maternal diabetes, the fetus is exposed to hyperglycaemia and hyperinsulinaemia both of which inhibit glycogenolysis Present address: * Department of Crop Science, University of Saskatchewan, Saskatoon, Saskatchewan Canada, S7N 0W0 9 * Faculty of Medicine, University of Manitoba, Winnipeg, Canada R3E 0W3 and reduce the formation of precursors for synthesis of surfactant phospholipids [9,[11][12][13]. While some investigators have reported reduced synthesis of surfactant phospholipids in lungs of fetuses of diabetic mothers [14,15] others have not observed any significant changes in the phospholipid synthesis [16,17].…”
mentioning
confidence: 99%
“…Many studies implicate insulin as an inhibitor of fetal lung maturation [6,71, although data are not consistent [8, 91. Substrate availability is important in fetal lung differentiation.…”
Section: Introduction Pulmonary Surfactant Deficiency Presenting As Rmentioning
confidence: 99%
“…Gross et al (10) have reported that insulin delays the morphologic maturation of fetal rat lung in organ culture, causing a decrease in the number of lamellar bodies in alveolar type II cells. In addition, Smith et al (11) have reported that insulin inhibits lecithin synthesis by cultured mixed fetal lung cells in the presence of glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%